2022
DOI: 10.1242/jeb.243947
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of learning walks related to scorpion home burrow navigation

Abstract: The Navigation by Chemotextural Familiarity Hypothesis (NCFH) suggests that scorpions use their midventral pectines to gather chemical and textural information near their burrows and use this information as they subsequently return home. For NCFH to be viable, animals must somehow acquire home-directed “tastes” of the substrate, such as through path integration (PI) and/or learning walks. We conducted laboratory behavioral trials using desert grassland scorpions (Paruroctonus utahensis). Animals reliably forme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Some have speculated that internal (idiothetic) mechanisms, such as information gathered by proprioceptors near leg joints [10] or by mechanoreceptors on the pectines [4,14,15], could aid the homeward return of scorpions via PI (Ortega-Escobar et al 2023 accepted). Proprioception has been shown to be important for PI in other arachnids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have speculated that internal (idiothetic) mechanisms, such as information gathered by proprioceptors near leg joints [10] or by mechanoreceptors on the pectines [4,14,15], could aid the homeward return of scorpions via PI (Ortega-Escobar et al 2023 accepted). Proprioception has been shown to be important for PI in other arachnids.…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that scorpions use such cues as prevailing winds or vision to return home [1]. However, more recent evidence suggests that scorpions may also use innate behaviors such as learning walks [4] and path integration [5] to find their burrows.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, many biological systems can compensate the loss of certain structures by other mechanisms. The pectines have been suggested to play an important role in navigation and homing (Gaffin et al, 2022; Gaffin & Brayfield, 2017). However, scorpions belonging to the species Mesobuthus eupeus have been shown to navigate well by using path integration without information processed by the pectines (Prévost & Stemme, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…They are proposed to be essential for detecting prey and finding mates (Gaffin & Brownell, 1992; Krapf, 1986; Melville, 2000; Melville et al, 2003; Steinmetz et al, 2004). Furthermore, recent discoveries of path integration (Prévost & Stemme, 2020) and learning walk performance (Gaffin et al, 2022) revealed that scorpions are able to realize complex navigational behaviours. Along these lines, Gaffin and Brayfield (2017) postulated the chemo‐textural familiarity hypothesis, which is based on the assumption that scorpions continuously gather substrate‐borne chemo‐ and mechanosensory information with their pectines to generate a complex image of their surroundings (for reviews on scorpion navigation see Gaffin & Curry, 2020; Ortega‐Escobar et al, 2023; Prévost & Stemme, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The pectines are hypothesized to serve as primary contact chemosensory organs due to the structure and position of the bimodal peg sensillae. While there is behavioral evidence that pectines are used in localization and trailing of prey and/or mates (Gaffin & Brownell, 1992;Krapf, 1986;Melville, 2000;Melville et al, 2003;Steinmetz et al, 2004), it seems that pectines are also involved in navigation and homing, by using bimodal cues from the environment, detected by the peg sensillae (Gaffin et al, 2022;Gaffin & Brayfield, 2017;Musaelian & Gaffin, 2020). Although successful homing in Mesobuthus eupeus (Koch, 1839) is not dependent on pecten or visual input but based on path integration (Prévost & Stemme, 2020), the integration of pecten information might allow for more precise navigation, a hypothesis recently supported by first evidence of learning walks in scorpions (Gaffin et al, 2022).…”
Section: Morphology and Function Of Scorpion Pectinesmentioning
confidence: 99%